Material Performance to Reduce the UHI (Urban Heat Island) Phenomenon at Deo Airport, Sorong City - Maryanto, Eko Tavip; Ruzuqi, Rezza (Universitas Ibn Khaldun Bogor, 2023)
Domine Eduard Osok Airport is a Class I Airport in the city of Sorong which is experiencing quite rapid development. This fairly rapid development has made airport managers think of ways to be able to provide maximum service to airport users. One of these services is to reduce the occurrence of the Urban Heat Island (UHI) phenomenon in the airport area by placing several types of materials around the airport. Several types of heat-absorbing materials are natural or synthetic materials that are used to withstand high temperatures. Nature provides a choice of materials that can be applied in this effort. Raw materials contained in nature will later be processed or used directly as an effort to reduce heat. The city of Sorong is a city that has problems with the occurrence of the UHI phenomenon because recently it has experienced an increase in population. To reduce the heat generated, various materials are used to be applied. These materials include Cast concrete, Asphalt, Soil, and Paving Materials. In this study, the material performance in reducing heat is determined for the four materials. The measuring instrument used is a measuring instrument commonly used to measure temperature. Measurements were made from morning to night. The results obtained are that cast concrete material has better performance compared to other types of materials when applied as a heat-absorbing material in buildings. Meanwhile, paving material is a good material if applied as a road material. With the average temperature produced for each material morning=25.20C, afternoon=26.20C, afternoon=26.60C, and night 25.90C and morning=32.70C, afternoon=33.90C, afternoon=29.00C, and night 28.8 0C.